Synthesis, structure and dispersion interactions in bis(1, 8-naphthalendiyl)distibine12. Issue 28 (5th July 2017) - Ganesamoorthy, C.; Heimann, S.; Hölscher, S.; Haack, R.; Wölper, C.; Jansen, G.; Schulz, S.
Abstract : Naph2 Sb2 1 shows intermolecular interactions in the solid state. Quantum chemical calculations of1 and the lighter (P, As) and heavier (Bi) congeners showed that intermolecular E⋯E interactions (E = P, As, Sb, Bi) are dispersion dominated, while E⋯π interactions additionally contained a significant electrostatic contribution. Abstract : Naph2 Sb2 1 was synthesized by a reaction of 1, 8-dilithionaphthalene NaphLi2 with SbCl3 and its solid state structure is reported on.1 shows intermolecular interactions in the solid state, which were studied by quantum chemical calculations with dispersion corrected density functional theory, supermolecular ab initio approaches and symmetry adapted perturbation theory. The same methods were employed to compare the solid state interactions in the crystal of1 to those in real (for E = P) and hypothetical (for E = As and Bi) crystal structures of Naph2 E2 . Dispersion interactions were found to provide the most important stabilising contribution in all cases, seconded by electrostatic attraction between pnictogen atoms and π-systems of neighbouring naphthyl groups.